Psychometric validation of the Hospital Stress Questionnaire - Daniel M. Ford; Rebecca Lawton; Elizabeth A. Teale; Daryl B. O’Connor (PLoS ONE, 2025)
Background Psychological stress experienced by inpatients has been shown to be associated with poorer post-hospital outcomes. Research that explores and intervenes to address in-hospital stress and ameliorate negative patient outcomes requires a valid measurement tool. The Hospital Stress Questionnaire (HSQ) was developed for this purpose. The aims of the current study were to psychometrically validate the HSQ, identify latent factors, reduce the number of items within the HSQ, and explore the psychometric properties of longer and shorter versions of the scale. Methods A nationally representative sample of recent NHS hospital inpatients (N =  660; mean age =  54.0, range =  18–97) completed the HSQ within a survey of patient experiences; 32 of which completed the measure a second time two weeks later. Factor structure, convergent validity, known-groups validity, predictive validity, and test-retest reliability were assessed. Results Seven domains of in-hospital stress were identified: quality of care, away from home, inconvenienced, health anxiety, negative effects of treatment, ward environment, and disrupted patient experience. Long (55 items), medium (28 items), and short (10 items) versions of the measure were produced, all exhibiting excellent psychometric properties. The highest rated stressor was “poor sleep”. Conclusion The HSQ is a valid and reliable tool, now available to be used by researchers and clinicians. It has potential to be used in intervention studies to reduce in-hospital stress, and to identify patients most at risk of the effects of post-hospital syndrome.